Decomposing Money: Ontological options and spreads. Issue 1 (2nd January 2016) - Bryan, Dick; Rafferty, Michael
Abstract : Debates about the nature and origin of the social foundations of money can have no closure. There is a range of credible, but sometimes inconsistent, positions. This paper conjectures that the framing of debates is itself precluding the recognition that these 'foundations' are themselves conjuncturally specific. At critical historical points of monetary crisis or innovation, it is the divergence between theories that gives analytical potence, for it reveals different aspects of social instability and change. Hence, the paper frames theories of the social foundations of money as presenting 'ontological spreads' which are generally quite narrow but widen at critical times when the social foundations of money show instability.